Tumor apparent diffusion coefficient value and ratio in magnetic resonance imaging on cervical cancer - Siregar, Trifonia Pingkan; Wanandi, Septelia Inawati; Darmiati, Sawitri; Kusuma, Fitriyadi; Sekarutami, Sri Mutya; Lisnawati; Prihartono, Joedo; Ilyas, Muhammad; Amalia, Ginva; Elfahmi, Khalida Ikhlasiya Tajdar Gefariena (Medical Journal of Indonesia, 2025)
BACKGROUND Diffusion-weighted magnetic resonance imaging (DW-MRI) is a noninvasive, non-contrast sequence for cancer detection. Research involving DW-MRI in cervical cancer has revealed lower apparent diffusion coefficient (ADC) values. This study aimed to evaluate the difference in tumor ADC values and ADC ratios (tumor-to-urine and tumor-to-muscle) with respect to tumor staging (early versus late) and histopathology (squamous cell carcinoma versus adenocarcinoma). METHODS This retrospective study included 56 patients with cervical cancer, divided into early- and late-stage groups. DW-MRI was performed in all patients, and the tumor ADC value, ADC ratio between the tumor and urine (ADC ratiot−u), and ADC ratio between the tumor and gluteal muscle (ADC ratiot−m) were measured. Statistical methods were employed to assess the difference in the tumor ADC value, ADC ratiot−u, and ADC ratiot−m with respect to cervical cancer stages and histopathological findings. RESULTS The median tumor ADC value was lower in the early-stage group than in the late-stage cervical cancer (0.75 × 10−3 mm²/s versus 0.8 × 10−3 mm²/s, p = 0.022). However, no differences were observed in ADC ratiot−u and ADC ratiot−m concerning the tumor staging, nor in ADC value, ADC ratiot−u, and ADC ratiot−m concerning histopathological findings (p = 0.29, 0.67 and 0.35, respectively), with no significant differences in the ADC ratiot−u (p = 0.153) and ADC ratiot−m (p = 0.260). In receiver operating characteristic analysis, the tumor ADC value was 75.0% sensitive and 50.0% specific in predicting late-stage cervical cancer with a cut-off value of 0.750 × 10−3 mm2/s. CONCLUSIONS The median tumor ADC value in early-stage patients was significantly lower than in the late-stage patients, suggesting that tumor ADC value has valuable potential for characterizing cervical cancer staging.